The Effect of Need for Achievement, Locus of Control, and Attitudes towards Student Entrepreneurial Intentions in SMKN 1 Batanghari - Herry Sofyandy Pranata; Khairinal Khairinal; Denny Denmar (Bina Nusantara University, 2021)
High unemployment rate, especially from SMK graduates, and the lack of entrepreneurship in Indonesia have prompted many parties to find out solutions. It is very important in fostering graduates who are ready to become entrepreneurs. The research aimed to investigate the influence of need for achievement, locus of control, and attitudes toward entrepreneurial intentions of students of SMK Negeri 1 Batang Hari. Data analysis method used path analysis in which multiple regression models were tested with classical assumptions to determine the appropriate analysis model. The classical assumption test included: normality test using the one-sample Kolmogorov-Smirnov test, homoscedasticity test using the Spearman’s Rho test, and linearity test using the lack of fit test and the multicollinearity test. With a sample of 175 class-XI students of all majors at SMKN 1 Batang Hari, the result shows that there is an influence of need for achievement, locus of control, and attitudes toward students’ entrepreneurial intention at SMK Negeri 1 Batang Hari.